Experimental Connection between ESG Scores and Key Financial Indicators : ROA, ROE AND TOBIN’S Q - Azrul Hazim, Fahrullah; Sharifah Sabrina, Syed Ali; Suzila, Mohamed Yusof; Nurul, Widya (UNIMAS Publisher, 2024)
This study explores the relationship between Environmental, Social, and Governance (ESG) practices and the financial performance of Malaysian listed firms, focusing on key financial indicators such as Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q (TQ). Using a quantitative approach, panel data from 30 publicly traded Malaysian companies between 2018 and 2020 was analysed through Ordinary Least Squares (OLS) and Generalized Least Squares (GLS) regression models. The findings demonstrate a significant positive relationship between ESG scores and ROA, indicating that firms with stronger ESG commitments tend to perform better in terms of asset returns. However, the relationship between ESG and ROE or Tobin’s Q is less conclusive, with mixed results across different model specifications. Variables such as firm size, leverage, and liquidity showed no consistent impact on financial performance. The study highlights the financial benefits of ESG adoption for Malaysian companies and provides insights for investors pursuing sustainable investment strategies. These findings offer practical implications for firms seeking to enhance their competitiveness by integrating ESG practices into their operations.